1961
DOI: 10.1172/jci104405
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Dynamics in Man Measured by Nonradioactive Strontium*

Abstract: A great deal of useful information about calcium metabolism in man has been obtained by balance technics. Balance studies give only net changes in total body calcium and do not indicate whether changes in balance result from alterations of rates of movement into or out of bone. For example, positive balance could result from increased bone deposition or decreased bone resorption. Similarly, balance could be unchanged if increased resorption were matched by increased deposition. Rates of bone deposition have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
24
1
2

Year Published

1963
1963
1984
1984

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(31 citation statements)
references
References 44 publications
4
24
1
2
Order By: Relevance
“…At least in the short term (the present study being conducted during the first 10 days of treatment) there is an elevation in Va noted in all four subjects; on the other hand, Wajchenberg, Pereira, Kieffer, and Ursic (23) noted a decrease in the fraction of dietary calcium absorbed after prolonged treatment (18 days) although their subjects varied their calcium intake between control and treatment periods and may have had an increased absolute value for Va. Also, there appears to be an increase in vt with treatment without any significant change in pool size (M1 + M2) being noted. No significant change in v,+ was apparent in the present studies, but Eisenberg (29) found it to be elevated after 6 wk of glucocorticoid therapy; however, Eisenberg and Gordan (21) Vw.. In any event, short-term glucocorticoid treatment did not increase the ratio of bone resorption to rapidly miscible pool turnover.…”
contrasting
confidence: 62%
See 1 more Smart Citation
“…At least in the short term (the present study being conducted during the first 10 days of treatment) there is an elevation in Va noted in all four subjects; on the other hand, Wajchenberg, Pereira, Kieffer, and Ursic (23) noted a decrease in the fraction of dietary calcium absorbed after prolonged treatment (18 days) although their subjects varied their calcium intake between control and treatment periods and may have had an increased absolute value for Va. Also, there appears to be an increase in vt with treatment without any significant change in pool size (M1 + M2) being noted. No significant change in v,+ was apparent in the present studies, but Eisenberg (29) found it to be elevated after 6 wk of glucocorticoid therapy; however, Eisenberg and Gordan (21) Vw.. In any event, short-term glucocorticoid treatment did not increase the ratio of bone resorption to rapidly miscible pool turnover.…”
contrasting
confidence: 62%
“…In early studies (19)(20)(21) Cae was often simplified to a single compartment, but it became apparent that at least two compartments were required to fit the first 10 days of data and compensate for excessive excretion of tracer during the intitial mixing phases (14). Three compartments have also been used (20, 22, (24) used PTA data for 20 days and included a slower fourth compartment in their analyses, as also considered by others (5,20).…”
mentioning
confidence: 99%
“…By estimating the rate of resorption in the rib from knowledge of the bone formation rate and the rib porosity, Wu, Jett, and Frost (12) found an absolute increase in endosteal resorption rate (the process accounting for most of the resorption in the vertebrae), although the intracortical resorption rate was found to be lower than normal. Studies with bone-seeking isotopes have shown that skeletal mineral accretion is normal or is decreased in proportion to the decreased skeletal mass (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…It was thought that radioactive strontium (Srr), which was more readily available and which can be detected more simply, might serve as a substitute tracer for Car. Early experiments (1)(2)(3) confirmed this notion in a general way, and several investigators (4)(5)(6)(7) have subsequently proceeded on the assumption that Sr behaves like Ca in the body. Although the urinary excretions of Sr and Ca were found to differ, it has been assumed or demonstrated that as far as the skeleton is concerned, differences in the biological behavior of Ca and Sr are small and perhaps negligible (4,(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 93%
“…Sr occurs in the body in only very small quantities, and its concentration in various tissues is known with only moderate precision (22). Analytical techniques for precisely analyzing small quantities of Sr have been developed only recently (5,7,23). In contrast with Ca studies, Sr concentration in kinetic studies with Srr has generally not been expressed in terms of specific activity (units of radioactivity per unit of mass), the only valid independent parameter.…”
mentioning
confidence: 99%